Evaluation of speech fundamental frequency and its range in normal farsi-speaking people of both sexes and across different ages via reading a passage - Asefeh Memarian; Sayed Amin Modareszade Esfahanifard (Vesnu Publications, 2012)
Introduction: Fundamental frequency has a critical role in the assessment of voice disorders. In fact it is one the most reported measures in clinical voice research. It is expected that voice pitch associates with many factors including age, gender, body size, race and social situation. Normative data for fundamental frequency have been considered as a standard criterion for determining the normality and abnormality of this parameter in people with voice disorders. Since there is a lack of standardized data pertaining to various voice parameters in normal speakers of Farsi, the aim of this present study was to determine the amount of Speech fundamental frequency and its range in male and female adults with normal voice at different ages. Materials and methods: In this study, 200 subjects with the age range of 20 to 59 years were studied cross-sectionally. The voice samples were recorded while subjects were reading "Rangin Kaman" passage. The obtained voice samples were then analyzed via "Real Analysis" program of Dr. Speech Software. All data of interest was statistically analyzed through t test. Results: Speech fundamental frequency and its range at different ages were higher in women than in men. Conclusion: In normal people, Speech fundamental frequency and its range have different characteristics with regard to different sexes and ages. These differences can be accounted for to some extent by anatomic and physiological mechanisms which are just a few factors among many to name. Keywords: Speech fundamental frequency, Voice, Reading, Farsi-speaking